ANALISIS KINERJA KEUANGAN PERUSAHAAN PADA PT BANK PEMBANGUNAN DAERAH PAPUA BERDASARKAN ANALISIS RASIO KEUANGAN - Ayu Indrawati; Daniel Nemba Dambe (JURNAL ULET (Utility, Earning and Tax), 2021)
The purpose of this study is to determine the financial performance of PT Bank Pembangunan Daerah Papua which is analyzed through financial reports based on ratio analysis. The method in this research is using descriptive method. The study used primary data obtained from PT Bank Pembangunan Daerah Papua for the period 2019-2020. The data analysis technique used in this research is data analysis techniques using profitability ratios. The results show that the financial statements of PT Bank Pembangunan Daerah Papua for 2019-2020 for the ratio of GPM, NPM and ROCE are in a healthy / stable condition. However, the ROA and ROE ratios are in bad/unhealthy conditions.